2021
DOI: 10.1016/j.aca.2021.338310
|View full text |Cite
|
Sign up to set email alerts
|

A novel One-pot rapid diagnostic technology for COVID-19

Abstract: Novel coronavirus disease (COVID-19) caused by SARS-CoV-2 is an ongoing global pandemic associated with high rates of morbidity and mortality. RT-qPCR has become the diagnostic standard for the testing of SARS-CoV-2 in most countries. COVID-19 diagnosis generally relies upon RT-qPCR-mediated identification of SARS-CoV-2 viral RNA, which is costly, labor-extensive, and requires specialized training and equipment. Herein, we established a novel one-tube rapid diagnostic approach based upon formamide and colorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Meanwhile, Li et al reported an extraction-free RT-LAMP method by incorporation of 6% formamide into reaction mixture. They managed to obtain 5 copies/μL within 45 min [ 15 ]. Wei et al reported a RT-LAMP based testing on RNA-spike samples by using an in-house lysis buffer.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Li et al reported an extraction-free RT-LAMP method by incorporation of 6% formamide into reaction mixture. They managed to obtain 5 copies/μL within 45 min [ 15 ]. Wei et al reported a RT-LAMP based testing on RNA-spike samples by using an in-house lysis buffer.…”
Section: Discussionmentioning
confidence: 99%
“…The human internal control primer, RPP20, also performed relatively well on human gene dilutions. Of note, we used an inactivated whole virus rather than synthetic RNA transcripts as the standard control; hence a higher limit of detection (LOD) compared to other studies reporting similar performance to RT-PCR with lower LOD [ 36 ]. Zhou et al [ 37 ] recently reported that a whole virus quantified by RT-ddPCR would provide an ideal reference standard for quality control assessment from nucleic acid extraction to detection.…”
Section: Resultsmentioning
confidence: 99%
“…Based on conventional LAMP, researchers developed the capture and improved loop‐mediated isothermal amplification (Cap‐iLAMP) method, which combines a hybridization capture‐based RNA extraction of gargle lavage samples with an improved colorimetric RT‐LAMP assay and smartphone‐based color scoring. Cap‐iLAMP enables the detection of SARS‐CoV‐2‐positive samples in less than one hour 65,66 . Compared with RT‐PCR, this method amplifies DNA with high specificity, efficiency, and rapidity, without the need for expensive instruments, under isothermal conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Cap‐iLAMP enables the detection of SARS‐CoV‐2‐positive samples in less than one hour. 65 , 66 Compared with RT‐PCR, this method amplifies DNA with high specificity, efficiency, and rapidity, without the need for expensive instruments, under isothermal conditions. These characteristics are a huge advantage for POCT.…”
Section: Methodsmentioning
confidence: 99%